2014
DOI: 10.1016/j.ejpe.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of some derivatives of polysiloxanes

Abstract: Silicone surfactants have been widely used in our daily life and many industrial fields on the basis of their unusual properties. Only in the past decades has the use of silicone as a hydrophobic building block for the preparation of surfactants become common. The recent trend to combine silicone, polyoxyalkylene and carbohydrate moieties in the same molecule has resulted in a plethora of new compounds with new properties.In this article, we report the preparation of a series of ''glycopolysiloxanes'' surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Under of an alternating magnetic field, iron is observed to heat as a result of losses occurring as a result of the internal rotation of the magnetization and the rotation of the particles in a viscous medium. Uniform is necessary to ensure an even heat distribution within the polymer matrix during the curing procedure [ 24 ]. The heat generated from samples was evaluated by exposing iron in PDMS to an alternating current (AC) magnetic field for certain time.…”
Section: Resultsmentioning
confidence: 99%
“…Under of an alternating magnetic field, iron is observed to heat as a result of losses occurring as a result of the internal rotation of the magnetization and the rotation of the particles in a viscous medium. Uniform is necessary to ensure an even heat distribution within the polymer matrix during the curing procedure [ 24 ]. The heat generated from samples was evaluated by exposing iron in PDMS to an alternating current (AC) magnetic field for certain time.…”
Section: Resultsmentioning
confidence: 99%
“…22−24 In the literature, it was already shown that dextran hardly decrease the surface tension of water (less than 1 mN/m for concentrated solution of dextran of 50g/ L), 25 whereas glucose functionalized polymers act as efficient dispersants (for instance, glycopolysiloxane solutions decrease the surface tension of water down to 35 mN/m). 26 Moreover, we cannot exclude that cross-linking by IPDI would be more effective on the glycopolymer than on polysaccharide, thus creating a chemical barrier against miglyol release.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In contrast, polysaccharide-coated oily particles only stabilized in size after 5–10 min. This contrasting behavior may be attributed to the marked amphiphilic character of the glycopolymer, whose preferred adsorption at the surface of the oily droplets would generate a compact polymer layer (hardly swollen) physically limiting miglyol diffusion by Ostwald ripening. In the literature, it was already shown that dextran hardly decrease the surface tension of water (less than 1 mN/m for concentrated solution of dextran of 50g/L), whereas glucose functionalized polymers act as efficient dispersants (for instance, glycopolysiloxane solutions decrease the surface tension of water down to 35 mN/m) . Moreover, we cannot exclude that cross-linking by IPDI would be more effective on the glycopolymer than on polysaccharide, thus creating a chemical barrier against miglyol release.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The crosslinking process alters the characteristic of the pre-polymer from viscous to elastic. The curing process may be accelerated by increasing the temperature [ 20 ]. After the completion of the crosslinking process, the PDMS composite exhibits a rubbery appearance.…”
Section: Resultsmentioning
confidence: 99%